Workers Protection with a Fixed-Term Employment Contract System based on the Employment Statutory Regulations - Muhammad Kamal (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2020)
This research aims to identify and understand the position of legal protection for workers with a system of fixed-term employment contracts in the aspects of work relations, protection, and wages based on Employment laws and regulations. This research uses an empirical normative research method which combines the normative legal approach with empirical research. The results of this study indicate that there are still many companies in Makassar City that do not implement statutory regulations, especially regarding workers 'rights, for example, workers' status based on fixed time or a Non-Specified term employment contract and wages that are not in accordance with the city's minimum standard. As for the conditions of the workers, based on the analysis result from the prescriptive aspect, there were 95 or 47.50% of 200 workers starting a cooperative relationship without making a written agreement. Furthermore, there are as many as 55 or 27.50% of 200 workers assess that in their work activities, they do not get rights, there are also as many as 110 or 55.00% of 200 workers do not know what the form of worker rights is. Furthermore, there were as many as 140 or 70.00% of the 200 workers who received compensation that did not match the minimum wage in 3 (three) companies in Makassar City. These problems can be resolved appropriately if Law no. 13 of 2003 is properly implemented by Labor Inspectors and Specialist Labor Inspectors as the person in charge based on Minister of Manpower Regulation (Permenaker) No. 33 of 2016.